2022
DOI: 10.1016/j.celrep.2021.110283
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro chronic damage model impairs inflammatory and regenerative responses in human colonoid monolayers

Abstract: Highlights d Repeated rounds of air-liquid interface growth and submergence damage human colonoids d Colonoids lose regenerative capacity with repeated injury d Repeated injury causes loss of inflammatory responsiveness to flagellin d Repeated injury causes changes in gene expression and DNA methylation resembling IBD Authors William D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…Based on that, we do not recommend combining cohorts of fresh and thawed organoid cultures in projects where comparative analysis between clinical groups of patients are planned. Single cells derived from dissociated organoids are also useful for generating those primary 2D cultures that had already shown high versatility in multiple applications when seeded on conventional plastic plates ( S3A Fig ), Transwell inserts ( S3B Fig ) or microfluidic chips [ 26 , 44 47 ]. In this case, we observed that more aggressive organoid dissociation, like the one mediated by trypsin, is also suitable for growing 2D cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Based on that, we do not recommend combining cohorts of fresh and thawed organoid cultures in projects where comparative analysis between clinical groups of patients are planned. Single cells derived from dissociated organoids are also useful for generating those primary 2D cultures that had already shown high versatility in multiple applications when seeded on conventional plastic plates ( S3A Fig ), Transwell inserts ( S3B Fig ) or microfluidic chips [ 26 , 44 47 ]. In this case, we observed that more aggressive organoid dissociation, like the one mediated by trypsin, is also suitable for growing 2D cultures.…”
Section: Resultsmentioning
confidence: 99%
“…A number of organoid-derived monolayer systems have been described recently [17][18][19][20][21][31][32][33][34][35][36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, stimulates the expression of immune factors such as TNF‐α, interferon‐γ (IFN‐γ), and IL‐10, ultimately exacerbating the severity of IBD 22 (Figure 1). The levels of methylation modification in the ER gene were higher in patients with IBD, suggesting that methylation may serve as a potential diagnostic marker for IBD 23 . In contrast, analysis of IBD patients found no evidence of DNA methylation in the IRF5 promoter region, indicating that IRF5 is unlikely to play a role in the development of IBD 19 .…”
Section: Epigenetic Modifications In Ibdmentioning
confidence: 91%
“…The levels of methylation modification in the ER gene were higher in patients with IBD, suggesting that methylation may serve as a potential diagnostic marker for IBD. 23 In contrast, analysis of IBD patients found no evidence of DNA methylation in the IRF5 promoter region, indicating that IRF5 is unlikely to play a role in the development of IBD. 19 Additionally, the dysregulation of IFN-γ, caused by increased DNA methylation of the IFN-γ gene in T cells from peripheral blood of IBD patients, contributed to IBD's exacerbation.…”
Section: Dna Epigenetic Modifications In Ibdmentioning
confidence: 94%